2014
DOI: 10.1177/0734371x14544546
|View full text |Cite
|
Sign up to set email alerts
|

Toward Representative Bureaucracy

Abstract: To deliver truly representative and effective democratic governance, a public service (PS) should employ individuals from diverse backgrounds throughout its workforce. In the Canadian government, patterns of underrepresentation persist for each of the four employment equity (EE) groups. This study explores three questions: First, are there differences between the four EE groups in terms of their attraction to jobs in the public sector? Second, what are key work values that predict PS attraction? Third, do EE g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
(76 reference statements)
0
13
1
Order By: Relevance
“…The author points out that especially visible minorities and groups -such as women and people of colour -hesitate to apply for positions in public sector employment because these groups often fear being subjugated to negative stereotypical behaviour. Ng and Sears (2015) present further empirical evidence from Canada showing that visible minorities often prefer private sector employment, implicitly assuming that the private workforce is less homogenous so they would be less likely to stand out. The authors argue that especially immigrants of visible ethnicity seek for the opportunity of rapid socioeconomic mobility, which they tend to associate with the private rather than the public sector.…”
Section: Self-selection (Attraction)mentioning
confidence: 80%
See 1 more Smart Citation
“…The author points out that especially visible minorities and groups -such as women and people of colour -hesitate to apply for positions in public sector employment because these groups often fear being subjugated to negative stereotypical behaviour. Ng and Sears (2015) present further empirical evidence from Canada showing that visible minorities often prefer private sector employment, implicitly assuming that the private workforce is less homogenous so they would be less likely to stand out. The authors argue that especially immigrants of visible ethnicity seek for the opportunity of rapid socioeconomic mobility, which they tend to associate with the private rather than the public sector.…”
Section: Self-selection (Attraction)mentioning
confidence: 80%
“…The first argumentative cluster used to explain workforce homogeneity in the public sector is self-selection. This micro-level perspective describes the measurable outcome of an individual's implicit or explicit preference to associate themselves with a group or sector based on tangible as well as non-tangible characteristics such as affect, perceived similarity (Ng and Sears 2015;Danzer 2019), ethical preferences (Ayaita, Yang, and Gülal 2019; Barfort et al 2019) but also parental socialization that prime homophily in job choice (Fischer and Schott 2020). As a result, individuals make employment choices that will eventually lead to their professional association with a public organization -as opposed to a private sector firm.…”
Section: Self-selection (Attraction)mentioning
confidence: 99%
“…Specifically, why should someone work for the government today other than for the generous benefits that come with the job?" Other scholars similarly suggest that the government must do more to create awareness about public sector employment opportunities and position it as an attractive career option (Ng and Sears, 2015). For example, in one study of nearly 20,000 Canadian university students, only 28.9 percent of the respondents indicated that they would choose public service over private sector employment while 33.1 percent identified the Government of Canada as an employer of choice (Ng and Gossett, 2013, p. 351).…”
Section: Canadian Federal Public Service Branding Initiativementioning
confidence: 99%
“…But this may result from self-sorting or from compliance with organizational norms, missions and code-of-ethics; public service motivation may be a stable personality trait (Vogel and Kroll, 2016) or a dynamic state induced by on-the-public-job socialization (Kjeldsen and Jacobsen, 2013). Among college students the link between self-reported prosocial motivation and the desire to work in nonprofit sectors has been studied in a wide range of administrative contexts and cultures, such as Northern America (Boyd et al: 2017; Choi and Chung, 2017; Clerkin and Coggburn, 2012; Lewis and Frank, 2002; Ng and Sears, 2015; Perry, 1997; Rose, 2010), Latin America (Sanabria-Pulido, 2017), Europe (Belle, 2015; Nezhina and Barabashev, 2017; Vandenabeele, 2008; Winter and Thaler, 2016), and Asia (Bangcheng et al, 2011; Banuri and Keefer, 2016; Ko and Jun, 2015). This extensive research indicates that the link between prosocial motivation and career interests varies between administrative contexts.…”
Section: Hypothesesmentioning
confidence: 99%